The Impact of Kindergarten Teachers’ Beliefs on the Implementation of Play-Based Learning (PBL) in China - Zhang Haihan; Mohd Nazri Abdul Rahman (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
Kindergarten teachers' beliefs play a vital role in the implementation of Play-Based Learning (PBL) pedagogy. This study aims to analyze the impact of teachers’ beliefs on the design, implementation, and evaluation of play-based pedagogy through semi-structured interviews with two public kindergarten teachers. The results show that teachers' beliefs directly affect the positioning of play in the curriculum, the selection of play content, and the combination with teaching objectives. Teachers' professional development and policy environment also play an important role in the formation and change of beliefs. This study provides practical suggestions for promoting the further development of play-based teaching in Early Childhood Education of Chian.